Graphene Oxide and Derivatives: The Place in Graphene Family - Dideikin, Artur T.; Vul', Alexander Y. (Frontiers in Physics, 2019)
Graphene oxide (GO) is useful and promising material for graphene based applications in electronic, optics, chemistry, energy storage and biology. At the beginning of graphene history GO was only a simple and cheap step for preparation of single and multilayer graphene films and bulk structures by reduction. The further studies revealed the substantial structure imperfection of graphene oxide derived materials due to the defects in initial graphite and incompletion of reducing process. However, the results of recent research demonstrated a great amount of unique chemical, optical and electronic properties of graphene oxide that allow regarding it as independent nanomaterial possessing a large area of applications. In general, it represents the ultra-large organic molecule containing 2D carbon mesh. Unlike conventional graphene it provides wide range of chemical methods for attachment of various functional groups to its surface for control optical transparency, electrical and thermal conductance. Recently developed methods for preparation of graphene oxide derivatives saturated by carboxyl groups open the new attractive application areas in green technologies including energy storage and utilizing nuclear wastes. The goal of the review is to summarize the results of recent studies of graphene oxide, derivatives and reveal the most promising directions to focus the efforts of researchers.